Molecular biodiversity of cassava begomoviruses in Tanzania: evolution of cassava geminiviruses in Africa and evidence for East Africa being a center of diversity of cassava geminiviruses - Ndunguru, J.; Legg, James P.; Aveling, T.; Thompson, G.; Fauquet, Claude M. (Springer, 2005)
Cassava is infected by numerous geminiviruses in Africa and India that cause devastating losses to poor farmers. We here describe the molecular diversity of seven representative cassava mosaic geminiviruses (CMGs) infecting cassava from multiple locations in Tanzania. We report for the first time the presence of two isolates in East Africa: (EACMCV-[TZ1] and EACMCV-[TZ7]) of the species East African cassava mosaic Cameroon virus, originally described in West Africa. The complete nucleotide sequence of EACMCV-[TZ1] DNA-A and DNA-B components shared a high overall sequence identity to EACMCV-[CM] components (92% and 84%). The EACMCV-[TZ1] and -[TZ7] genomic components have recombinations in the same genome regions reported in EACMCV-[CM], but they also have additional recombinations in both components. Evidence from sequence analysis suggests that the two strains have the same ancient origin and are not recent introductions. EACMCV-[TZ1] occurred widely in the southern part of the country. Four other CMG isolates were identified: two were close to the EACMV-Kenya strain (named EACMV-[KE/TZT] and EACMV-[KE/TZM] with 96% sequence identity); one isolate, TZ10, had 98% homology to EACMV-UG2Svr and was named EACMV-UG2 [TZ10]; and finally one isolate was 95% identical to EACMV-[TZ] and named EACMV-[TZ/YV]. One isolate of African cassava mosaic virus with 97% sequence identity with other isolates of ACMV was named ACMV-[TZ]. It represents the first ACMV isolate from Tanzania to be sequenced. The molecular variability of CMGs was also evaluated using partial B component nucleotide sequences of 13 EACMV isolates from Tanzania. Using the sequences of all CMGs currently available, we have shown the presence of a number of putative recombination fragments that are more prominent in all components of EACMV than in ACMV. This new knowledge about the molecular CMG diversity in East Africa, and in Tanzania in particular, has led us to hypothesize about the probable importance of this part of Africa as a source of diversity and evolutionary change both during the early stages of the relationship between CMGs and cassava and in more recent times. The existence of multiple CMG isolates with high DNA genome diversity in Tanzania and the molecular forces behind this diversity pose a threat to cassava production throughout the African continent.